Amanitin and phallotoxin concentration in Amanita phalloides var. alba mushroom - SEVEROĞLU, ZEKİ (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
Although rarely seen, Amanita phalloides var. alba, a variety of A. phalloides type mushrooms, causes mushroom poisoning resulting in death. Since it is frequently confused with some edible mushrooms due to its white colored cap and macroscopic appearance, it becomes important in toxicological terms. Knowledge of the toxin amount contained in this mushroom type is invaluable in the treatment of cases involving poisoning. In this study, we examined the toxin levels of various parts of the A. phalloides var. alba mushroom growing Duzce region of Turkey. Toxin analyses were carried out for A. phalloides var. alba, which were collected from the forests Duzce region of Turkey in 2011, as a whole and also separately in its spore, pileus, gills, stipe and volva parts. The alpha amanitin, beta amanitin, gamma amanitin, phalloidin and phallacidine analyses of the mushrooms were carried out using the RP-HPLC method. A genetic analysis of the mushroom showed that it had similar genetic characteristics as A. phalloides and was a variety of it. The lowest toxins quantity was detected in spores, volva and stipe among all parts of the mushroom. The maximum amount of amatoxins was measured in the gills. The pileus also contained a high amount of amatoxins. Generally, amatoxins and phallotoxin concentrations were lower as compared to A. phalloides, but interestingly all toxins other than gamma toxin were higher in the spores of A. phalloides var. alba. The amount of toxin in all of its parts had sufficient concentrations to cause death. With this study, the amatoxin and phallotoxin concentrations in A. phalloides var. alba mushroom and in its parts have been revealed in detail for the first time. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Amanitin; Phalloidin; Amanita phalloides var. alba; HPLC; BETA-AMANITIN; ALPHA-AMANITIN; GAMMA-AMANITIN; RENAL-FAILURE; AMATOXIN; TOXICITY; TISSUES; TOXINS